1979
DOI: 10.1038/281386a0
|View full text |Cite
|
Sign up to set email alerts
|

Orthotopic bone induction at sites of Moloney murine sarcoma virus inoculation in mice

Abstract: Moloney murine sarcoma virus (M-MSV) induces at the site of inoculation in newborn and adult mice and rats various types of sarcoma, including osteosarcoma. The induced tumours are fatal in newborn, whereas sarcomas developed in adult animals regress spontaneously. The regression is mediated mainly by a cellular response. We have now demonstrated that the presence of sarcomas induced by M-MSV is a powerful stimulus for periosteal osteogenesis around tumour masses. Orthotopically induced osteogenesis by M-MSV m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Periosteal bone induction is initiated by cells residing in the periosteal membrane, which are activated by growth factors that are released during immune-mediated spontaneous regression of the tumor MSV-induced [1,28], or by lesions elicited by the T cell mitogen Concanavalin A [29]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Periosteal bone induction is initiated by cells residing in the periosteal membrane, which are activated by growth factors that are released during immune-mediated spontaneous regression of the tumor MSV-induced [1,28], or by lesions elicited by the T cell mitogen Concanavalin A [29]. …”
Section: Discussionmentioning
confidence: 99%
“…Thus, the process of periosteal bone formation recapitulates both endochondral and intramembranous osteogenesis, the last type dominating. The newly formed bone collar is firmly attached to maternal bone and is very slowly resorbed by osteoclasts, so in some cases an increment of bone mass, sometimes exceeding 100% of the original mass, persists for several months post sarcoma development [1]. …”
Section: Introductionmentioning
confidence: 99%
“…The Department, the largest among similar Departments in the remaining Polish Medical Schools, has also conferred the highest number of Doctor of Medicine degrees and Professor titles. The scientific interests of the Department have concentrated, among other subjects, on in vitro induction of osteogenesis by various tissues, Maloney sarcoma virus and factors stimulating secretion of cytokines (Wlodarski, 1969;Wlodarski et al, 1979), and on various aspects of structure and organisation of skeletal tissues (Ostrowski et al, 1991(Ostrowski et al, , 1993. The group headed by Professor Moskalewski studied histogenesis of cartilage in vivo and in vitro and showed that individual chondrocytes are able to reconstitute the cartilage when transplanted into a recipient (Moskalewski, 1965;Moskalewski and Kawiak, 1965;Moskalewski et al, 1975Moskalewski et al, ,1983.…”
Section: Warszawamentioning
confidence: 99%
“…Some factors, such as certain viruses or transforming growth factor-~ promote orthtopic periosteal bone formation (12)(13)(14). Osteogenic reaction in these factors results exclusively in cell proliferation in the cambium layer of the periosteum.…”
Section: ( 152 )mentioning
confidence: 99%